A novel analytical ultracentrifugation based approach to the low resolution structure of gum arabic. Issue 9 (September 2016) - Gillis, Richard B.; Adams, Gary G.; Alzahrani, Qushmua; Harding, Stephen E.
ABSTRACT: Under investigation are the structural properties of gum arabic, an industrially important biopolymer for use as a stabilizer or in drug delivery, using Analytical Ultracentrifugation—a well‐established, matrix‐free probe for macromolecular size and shape. These results are combined with chromatographically‐coupled methods (multi‐angle light scattering, differential press imbalance viscometry) to provide a global analysis of its structure in varying ionic strength conditions. This analysis indicates that gum Arabic may have a compact, elliptical structure in solution, the significance of which for biotechnological use is indicated. This modelling method can be applied to other biopolymers and synthetic polymers. © 2016 Wiley Periodicals, Inc. Biopolymers 105: 618–625, 2016.